The impact of air pollutants on the risk of goiter based on a 9-year time series data - Du, Yanbin; Zhou, Hua; Chen, Yang (Frontiers in Public Health, 2025)
BackgroundWith the rapid advancement of industrialization and urbanization, air pollution is becoming increasingly serious, posing a huge threat to human health. There is limited literatures to study the relationship between air pollution and thyroid diseases. Therefore, this study aims to investigate the association between air pollutions (PM2.5, PM10, SO2, NO2, O3, and CO) and thyroid goiter.MethodsA 9-year time series data was collected from the Luoyang Air Testing Website from 2014 to 2022. A generalized additive model (GAM) based on Poisson regression was established and stratification analysis were used to explore the differences in the population by gender, age, place of residence, and season.ResultsThere were 37,630 hospital admissions for goiter in Luoyang from January 1, 2014 to July 30, 2022. Among them, there are 29,571 female (78.58%) and 8,059 male (21.42%); There are different lag effects of air pollutants on the thyroid goiter, and the relative risk (RR) of thyroid goiter showed a non-linear increasing trend with the increase of pollutants concentration on the optimal lag day. A 10 μg/m3 increase in PM2.5, PM10, O3, and NO2 concentrations (1 mg/m3 increase in CO) was associated with a 1.0092%(95%CI: 1.0032–1.015), 1.0044% (95%CI: 1.0008–1.0081), 0.9928%(95%CI: 0.9867–0.9988), 1.0596% (95%CI: 1.0413–1.0783) and 1.624%(95%CI: 1.1347–2.3243) risk of thyroid goiter, respectively. Besides, the effect of SO2 on goiter was not statistically significant. The stratified analysis results showed that women, age >45 years old, and urban populations may be more sensitive to pollutants, and people may be more sensitive to pollutants in autumn.ConclusionsThis time-series study suggested that long-term exposure to air pollutions may be associated with an increased risk of thyroid diseases, especially NO2 and CO have a greater impact on goiter than PM. These associations were stronger for patients more than 45 years old and during the autumn, especially for women. These findings suggest the importance of reducing air pollutant concentrations and protecting the environment.